The Influence of Discipline and Responsibility on Self Awareness of OHS Implementation in Mechanical Engineering Education Practical Courses at Sriwijaya University - Narayana Vijaya, I Made Veda; Yadi, Farhan (Journal of English Language and Education, 2025)
This study aims to determine the influence of discipline and responsibility on students' self-awareness in the implementation of Occupational Health and Safety (OHS) in practical lectures at the Mechanical Engineering Education Study Program, Sriwijaya University. The background of this study is based on the low awareness of students in implementing OHS, particularly in the use of personal protective equipment (PPE) when conducting practical work in the laboratory. Self-awareness, as an individual's ability to recognize and evaluate oneself, plays a crucial role in enhancing discipline and responsibility in the context of workplace safety. This study employs a quantitative approach using a survey method, distributing questionnaires to students from the 2022 and 2023 cohorts, with the sample size determined using the Slovin formula. The instruments used include validated indicators of discipline, responsibility, and self-awareness. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) to determine the relationships and influences between variables. The results of the study indicate that both discipline and responsibility have a positive and significant influence on students' self-awareness in implementing OSH. The combination of these two variables also contributes more significantly to enhancing self-awareness. This study is expected to provide practical contributions to improving the implementation of OSH in practical academic settings and serve as a reference for the development of policies and learning strategies based on workplace safety in higher education institutions.